Lipid Profile in Early and Late Stage among Patients with Nephrotic Syndrome-Related Chronic Kidney Disease in Dr. Hasan Sadikin General Hospital Bandung, Indonesia in 2016−2019 - Haya Hanif Mahardika; Ahmedz Widiasta; Viramitha Kusnandi Rusmil (Althea Medical Journal, 2023)
Background: Chronic kidney disease (CKD) is a major health problem in children with an increased prevalence globally. CKD is strongly associated with Nephrotic Syndrome (NS) and dyslipidemia, which become a progressive factor of CKD. This study aimed to describe the lipid profile of children with CKD and NS in Dr. Hasan Sadikin General Hospital Bandung, Indonesia.Methods: An observational-retrospective study was conducted with a cross-sectional design involving 150 medical records of children aged 1−18 years who were diagnosed with CKD with NS. Lipid profile data, including total cholesterol, triglycerides, LDL, and HDL, were collected from 2016−2019 using the total sampling method. Subjects with incomplete lipid profile data were excluded from the study.Results: Among the fifty-two children that were eligible and fulfilled the inclusion criteria, 88.5% were diagnosed with stage 1 CKD, and 32.7% were aged between 6−11 years and boys were predominant (67.3%). Lipid profile changes were found in the LDL, HDL, and total cholesterol serum levels between CKD stage I and II–V.Conclusions: Lipid profile of CKD pediatric patients with NS in Dr. Hasan Sadikin General Hospital Bandung in 2016−2019 showed hypertriglyceridemia and hypercholesterolemia. Most subjects were in stage I of CKD and Steroid-Resistant Nephrotic Syndrome, and comparison between stages of CKD and types of nephrotic syndrome is lacking. A prospective analytical study would be more reliable in proofing its significance.